2021
DOI: 10.3389/fmars.2021.686065
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Impacts of COVID-19 on a Tropical Lobster Fishery’s Harvest Strategy and Supply Chain

Abstract: The Torres Strait tropical rock lobster Panulirus ornatus (TRL) fishery is of immense social, cultural and economic importance to the region’s Indigenous fishers from both Australia and Papua New Guinea (PNG). During 2020, the COVID-19 pandemic indirectly impacted this fishery as well as a number of other fisheries reliant on international export markets. The TRL fishery is managed using an empirical (data-based) Harvest Control Rule (eHCR) to rapidly provide a recommended biological catch (RBC), based on catc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…The decline in fishing in the sea is due to the decrease in international demand for fish. The same is true of other countries (Plagányi et al, 2021) The resulting impact is the increasing quantity of fish in the ocean, especially in the south of Java, which has been overexploited. Furthermore, there is an improvement in the pollution content in the atmosphere.…”
Section: Atmospheric Pollution Trendmentioning
confidence: 94%
See 1 more Smart Citation
“…The decline in fishing in the sea is due to the decrease in international demand for fish. The same is true of other countries (Plagányi et al, 2021) The resulting impact is the increasing quantity of fish in the ocean, especially in the south of Java, which has been overexploited. Furthermore, there is an improvement in the pollution content in the atmosphere.…”
Section: Atmospheric Pollution Trendmentioning
confidence: 94%
“…The decrease was also caused by the reduced demand for fish exports from Indonesia. Previous research had also suggested that export demand from Australia to other countries was decreased during the pandemic (Plagányi et al, 2021). In the ocean, noise could be generated by water column dynamics and human activities such as ship engines (Erbe et al, 2020).…”
Section: Noise In the Oceanmentioning
confidence: 99%
“…There are concerns of aquaculture products by hindering fish supply from farmers to consumers. The COVID-19 outbreak has had great impacts on seafood supply chains [70]. The protection measures against the spread of COVID-19 have directly affected each step of fish harvesting, marketing, and exporting that may undermine the economic viability of aquaculture (Table 1).…”
Section: Farm To Plate: Disruption In Fish Supplymentioning
confidence: 99%
“…These measures disrupted fisheries production and scientific activity by restricting operational activities and movement of product and people (Asante et al 2021 ; Sorensen et al 2020 ), limiting supply of inputs to both fish harvesting and research activities (Chang et al 2022 ), de-coupling freight links to markets (Carlson, et al 2021 ), and dampening seafood demand (Fernandez-Gonzalez et al 2021 ; Giannakis et al 2020 ). Further knock-on effects identified include negative feedbacks on fisheries assessment and harvest settings arising from limited supply of fishery dependent data due to reduced fishing effort (Haas et al 2021 ; Link et al 2021 ; Plagányi et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%